2010
DOI: 10.1111/j.1365-2362.2010.02294.x
|View full text |Cite
|
Sign up to set email alerts
|

Thromboangiitis obliterans and endothelial function

Abstract: Acute TAO is characterised by vasoconstriction and increased aortic stiffness in the absence of changes in flow-mediated dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…A recent study comparing ten TAO patients in the acute phase and ten age-and sex-matched healthy subjects showed that TAO patients have a smaller brachial artery diameter with concentric and eutrophic remodelling and increased aortic stiffness. These differences are consistent with a diffuse and unopposed increase in vasomotor tone in the conduit arteries of the entire arterial system (Azizi et al 2010).…”
Section: Aetiologysupporting
confidence: 78%
“…A recent study comparing ten TAO patients in the acute phase and ten age-and sex-matched healthy subjects showed that TAO patients have a smaller brachial artery diameter with concentric and eutrophic remodelling and increased aortic stiffness. These differences are consistent with a diffuse and unopposed increase in vasomotor tone in the conduit arteries of the entire arterial system (Azizi et al 2010).…”
Section: Aetiologysupporting
confidence: 78%
“…Importantly, the response of the brachial artery wall to nitroglycerine administration remained unchanged, suggesting that dilatation dysfunction results predominantly from endothelial injury. In contrast, Azizi et al [29] did not observe altered responsiveness of the brachial artery to ischemia, although they documented higher rigidity of the aorta in TAO patients.…”
Section: Injury To the Vascular Endothelium And Activation Of The Infmentioning
confidence: 82%
“…ICAM-1 is expressed on the vascular endothelium and binds to the ligand to promote the firm adhesion between monocytes and endothelial cells (1618). Moreover, ICAM-1 is highly expressed in TAO, which is closely related to the TAO-induced increased expression of inflammatory factors, such as IL-1β, IL-6 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%